Evaluation of the Differences between Axial and Double Oblique Measurements of the Ascending Aorta on Gated, Contrast-Enhanced Thoracic Computed Tomography Scans: A Technical Note - Stark, Paul; Chang, Eric Y. (AORTA, 2024)
The purpose of the study was to compare axial measurements of the ascending thoracic aorta on gated CT study studies with double oblique measurements and calculate the divergence between orthogonal axial and double oblique diameters of the tubular ascending aorta.Retrospective measurements of axial and double oblique diameters were obtained in 153 consecutive patients.On average, the axial dimension exceeded the double oblique measurement.Our study endorsed the subtraction of 0.58 mm from the axial diameter in order to obtain the double oblique measurement.
Keywords: CT; tubular ascending aorta; dimensions; axial; double oblique